2017
DOI: 10.1186/s13046-017-0515-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex-determining region Y-box protein 3 induces epithelial-mesenchymal transition in osteosarcoma cells via transcriptional activation of Snail1

Abstract: BackgroundThe transcription factor sex-determining region Y-box protein 3 (SOX3) plays important roles in various types of cancer. However, its expression and function have not yet been elucidated in osteosarcoma (OS).MethodsThe expression levels of SOX3 in OS tissues and OS cell lines were determined by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot analysis. The effects of SOX3 expression on OS cell biological traits were investigated by overexpressing and downregulating SOX3 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Epithelial-mesenchymal transition (EMT) is a process integral to metastatic progression wherein tumor cells shed their epithelial-like properties and instead acquire more motile mesenchymal characteristics. EMT induction is critical to malignant cell dissemination in the context of OS progression (18,19), and EMT-regulating transcription factors including the zinc-finger-binding transcription factors Snai1 and Slug, zinc finger E−box −binding homeobox 1 (ZEB1), and the Twist1 and Twist2 basic helix-loop-helix (bHLH) factors have been shown to control this process in OS cells and to regulate associated metastasis (20)(21)(22). Integrins, which are heterodimeric receptors with a and b subunits that bind to the extracellular matrix, also regulate tumor malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a process integral to metastatic progression wherein tumor cells shed their epithelial-like properties and instead acquire more motile mesenchymal characteristics. EMT induction is critical to malignant cell dissemination in the context of OS progression (18,19), and EMT-regulating transcription factors including the zinc-finger-binding transcription factors Snai1 and Slug, zinc finger E−box −binding homeobox 1 (ZEB1), and the Twist1 and Twist2 basic helix-loop-helix (bHLH) factors have been shown to control this process in OS cells and to regulate associated metastasis (20)(21)(22). Integrins, which are heterodimeric receptors with a and b subunits that bind to the extracellular matrix, also regulate tumor malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the allelic heterogeneous mutations detected in PMC42-LA have also been associated with EMT drivers or markers; we identified novel mutations in GSN (R397W), WNT1 (T363K), SNAI2 (K188N), ITGA4 (R565W), SOX3 (R22P) and NID2 (G426E) (Supplementary Table S7). SNAI2-null mice are reported to have retarded epithelial migration rates [79], and SOX3 has been implicated in the malignant behaviour of glioblastoma [80], EMT, and in the promotion of migration and invasion of osteosarcoma cells [81,82]. A N161K mutation in SOX3 was found associated with progression of SCLC along with other mutated SOX members [83].…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al [47] identified SOX3 as a metastasis-associated gene in OS, highlighting its mechanistic connection with the TFs SNAIL1 and MET. SOX3 was overexpressed in 42 cases of human OS tissues in comparison with non-tumor samples.…”
Section: Sox3 and Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%